The Influence Of Emotional Intelligence, Spiritual Intelligence, Special Performance Assessment, Education, Training, And Motivation On Teacher Performance - Rizqi Syaroh Amaliyah (Return : Study of Management, Economic and Bussines, 2022)
Backgrounds: The concept of human development or human capital is a hot topic that is being widely discussed, considering that human capital is part of human resource management with a broader scope of study which addresses the practical side of human resource management. Aim: Between emotional intelligence, spiritual intelligence, special performance appraisal, education and training, and motivation on teacher performance (3) The simultaneous effect of emotional intelligence, spiritual intelligence, special performance appraisal, education and training, and motivation on teacher performance. Method: Using a quantitative approach and multiple linear regression analysis techniques. Findings: Based on the results of NJI calculations, all variables in this study are in the high category, meaning that each variable is perceived as good by the permanent teachers of the foundation. The results showed that the variables of emotional intelligence, spiritual intelligence, special performance appraisal, education and training, motivation partially had a positive and significant effect on teacher performance. Then simultaneously the variables of emotional intelligence, spiritual intelligence, special performance appraisal, education and training, motivation affect performance